The Withdrawal : Iraq, Libya, Afghanistan, and the Fragility of U.S. Power - Chomsky, Noam and Prashad, Vijay (New York The New Press, 2022)
"Not since the last American troops left Vietnam have we faced such a sudden vacuum in our foreign policy--not only of authority, but also of explanations of what happened, and what the future holds. Few analysts are better poised to address this moment than Noam Chomsky and Vijay Prashad, intellectuals and critics whose work spans generations and continents. Called "the most widely read voice on foreign policy on the planet" by the New York Times Book Review, Noam Chomsky is the guiding light of dissidents around the world. In The Withdrawal, Chomsky joins with noted scholar Vijay Prashad--who "helps to uncover the shining worlds hidden under official history and dominant media" (Eduardo Galeano)--to get at the roots of this unprecedented time of peril and change. Chomsky and Prashad interrogate key inflection points in America's downward spiral: from the disastrous Iraq War to the failed Libyan intervention to the descent into chaos in Afghanistan. As the final moments of American power in Afghanistan fade from view, this crucial book argues that we must not take our eyes off the wreckage--and that we need, above all, an unsentimental view of the new world we must build together." -- Front jacket flap
Keywords: United States -- Afghanistan -- Pakistan